Is hypomelanosis of Ito a generalized achromic nevus? - Di Lernia, V. (European Journal of Pediatric Dermatology, 2018)
Achromic nevus, also denominated hypochromic nevus or nevus depigmentosus, is a malformation often detected at birth representing about 0.4% of all pediatrie dermatoses (1). It is a hypochromic or achromic macular patch which is generally well circumscribed and presents a smooth surface and indented outlines. The lesion is generally single, though in rare cases can be multiple, and reddens after rubbing. It is usually localized on the trunk or in correspondence of the proximal extremities and is observed with the same frequency in both sexes.(...).